2018
DOI: 10.1038/s41467-018-06629-9
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional catalytic effects of black phosphorus quantum dots in shuttling-free lithium sulfur batteries

Abstract: Lithium sulfur batteries with high energy densities are promising next-generation energy storage systems. However, shuttling and sluggish conversion of polysulfides to solid lithium sulfides limit the full utilization of active materials. Physical/chemical confinement is useful for anchoring polysulfides, but not effective for utilizing the blocked intermediates. Here, we employ black phosphorus quantum dots as electrocatalysts to overcome these issues. Both the experimental and theoretical results reveal that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
236
1
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 348 publications
(250 citation statements)
references
References 71 publications
12
236
1
1
Order By: Relevance
“…As is known, the LiPSs shuttle mainly happens during the transformation of S 8 to long‐chain LiPS (high discharge voltage) . The high Q H reservation indicates shuttle effect has been efficiently suppressed . Correspondingly, Q L decreases from 668 mAh g −1 to 575, 505, and 475 mAh g −1 , with a capacity retention of 86, 76, and 71%, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As is known, the LiPSs shuttle mainly happens during the transformation of S 8 to long‐chain LiPS (high discharge voltage) . The high Q H reservation indicates shuttle effect has been efficiently suppressed . Correspondingly, Q L decreases from 668 mAh g −1 to 575, 505, and 475 mAh g −1 , with a capacity retention of 86, 76, and 71%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The rate capacity was further analyzed by separating the discharge/charge profiles of different C‐rates into two parts, including capacity contributed by the higher‐discharge plateau (>2.0 V, Q H ) and that of the lower‐discharge plateau (<2.0 V, Q L ). Q H value relates to the conversion of S 8 to long‐chain LiPS (solid‐to‐liquid), while Q L value corresponds to the conversion of soluble LiPS to solid lithium sulfide, Li 2 S 2 and/or Li 2 S (liquid‐to‐solid and/or solid‐to‐solid) . Theoretically, Q H equals to 419 mAh g −1 and Q L is 1256 mAh g −1 , corresponding to Q L / Q H = 3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also reported that employing hierarchical N-doped carbon nanocages (hNCNC) to encapsulate sulfur as the cathode, the Li-S batteries showed excellent durability after 1000 cycles at 10 A g −1 with a capacity of 438 mAh g −1 . [31] Guo et al fabricated a highly uniform 3D hierarchical N-doped carbon nanoflower (NCNF) as shown in Figure 1b, which displays a high surface area (907 m 2 g −1 ) and large pore volume (1.85 cm 3 g −1 ), thereby acquiring high activities in oxygen reduction reaction and Li-S batteries.…”
Section: Single Heteroatom-doped Configurationmentioning
confidence: 99%
“…b) The synthetic procedure schematic diagram and the reaction mechanism model of three dimensions hierarchical NCNF. Reproduced with permission [31] Copyright 2018, Springer Nature. [29] Copyright 2017, Royal Society of Chemistry.…”
Section: Co-doped Configurationmentioning
confidence: 99%